Peer Review of an Article: Tips, Tricks, and Troubleshooting - Rengarajan Rajagopal; Binit Sureka (Indian Journal of Radiology and Imaging)
Scientific publications are rapidly increasing in number, placing growing pressure on academics to publish. This study highlights the important tips and tricks for the authors in the context of reviewers' feedback and how to manage the article till the final stage of publication.